2016
DOI: 10.29121/granthaalayah.v4.i2.2016.2828
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characterization of Six Wheat Genotypes for Drought Tolerance

Abstract: Pakistan is one of the most severely affected countries by Global climate change, it is an agriculture based country and its economy (21%) mainly depend on agriculture production. Wheat is the major staple food crop in Pakistan and takes key position in the national economy. It contribute 12.5% share in agriculture and 2.9% in the country’s GDP. Frequent droughts and scarcity of the water severely affecting the wheat production. To fulfill the feed requirements of rapidly growing population, it is necessary to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…NRA activity varied from 11.40 µmol g -1 h -1 NO 2 (CO8) to 24.85 µmol g -1 h -1 NO 2 (VBN2) in control while in stressed plant it varied from 23.32 µmol g -1 h -1 NO 2 (CO6) to 47.42 µmol g -1 h -1 NO 2 (VBN2) (Fig 8). Muhammad et al, (2016) reported that NRA decreased with increasing water stress, maximum NRA were recorded at control level as compared to terminal drought in wheat genotypes.…”
Section: Nitrate Reductase Activity (Nra)mentioning
confidence: 93%
“…NRA activity varied from 11.40 µmol g -1 h -1 NO 2 (CO8) to 24.85 µmol g -1 h -1 NO 2 (VBN2) in control while in stressed plant it varied from 23.32 µmol g -1 h -1 NO 2 (CO6) to 47.42 µmol g -1 h -1 NO 2 (VBN2) (Fig 8). Muhammad et al, (2016) reported that NRA decreased with increasing water stress, maximum NRA were recorded at control level as compared to terminal drought in wheat genotypes.…”
Section: Nitrate Reductase Activity (Nra)mentioning
confidence: 93%
“…Potassium is also responsible in activating nitrate reductase; an enzyme critical for the production of protein in plants, regulating photosynthesis, water use efficiency, nitrogen uptake and protein building (Mandi et al, 2018;Nguyen et al, 2002). However, nitrate reductase is known to be sensitive to water stress because its metabolic pathway is regulated by water (Chachar et al, 2016;Lisar et al, 2012;Mujtaba et al, 2016;Zakariyya & Indradewa, 2018). Cakmak (2005) further provided an explanation for the increased need for K by plants suffering from drought stress.…”
Section: Role Of Potassium (K) In Plants Under Water Stress (Drought) Conditionmentioning
confidence: 99%
“…Drought stress is responsible for either inhibition or delayed seed germination or seedling establishment (Balkan and Gençtan, 2013). It has negative effects on the morphological, physiological, and biochemical attributes of the wheat crop (Chachar et al, 2016) and it results in a significant reduction in overall production (Bilal et al, 2015 andAbid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%